2020
DOI: 10.3390/jcm9113708
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Sense of Coherence, and Interpersonal Violence during the COVID-19 Pandemic Lockdown in Germany

Abstract: Preliminary data indicates that the Coronavirus SARS-CoV-2 disease (COVID-19) pandemic may have a substantial impact on mental health and well-being. We assessed mental health in response to the lockdown in Germany between 1 April 2020 and 15 April 2020 using a cross-sectional online survey (n = 3545) with a mixed-methods approach. We found increased levels of psychosocial distress (Patient Health Questionnaire (PHQ) stress module), anxiety, depressive symptoms (PHQ-4), irritability, and a decrease in overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 31 publications
5
73
0
9
Order By: Relevance
“…This finding is in line with our Hypothesis 1 as lower levels of well-being were expected during the current COVID-19 pandemic. A recently published empirical study reporting on mental health during the COVID-19 pandemic in Germany has similarly found an overall decrease in well-being measured with the WHO-5 [ 43 ]. In light of staggering preexisting mental health gradients between LGBTQIA* and cis-heterosexual people in Germany–documented just prior to the pandemic [ 21 ]–the findings of the current study are alarming.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with our Hypothesis 1 as lower levels of well-being were expected during the current COVID-19 pandemic. A recently published empirical study reporting on mental health during the COVID-19 pandemic in Germany has similarly found an overall decrease in well-being measured with the WHO-5 [ 43 ]. In light of staggering preexisting mental health gradients between LGBTQIA* and cis-heterosexual people in Germany–documented just prior to the pandemic [ 21 ]–the findings of the current study are alarming.…”
Section: Discussionmentioning
confidence: 99%
“…These mental health effects were predicted by pandemic-related fear, while trust in the government's actions and subjective level of information predicted a weaker increase in mental strain. Higher levels of psychosocial distress, depressive symptoms and anxiety were also found in a large cross-sectional survey ( N = 3545) focusing on the lockdown in Germany between 1 and 15 April [ 33 ]. Furthermore, the survey revealed higher levels of irritability and a decrease in sense of coherence, sexual contentment, overall well-being and sleep quality.…”
Section: Evidence From the German Health Sectormentioning
confidence: 92%
“…The adverse effects of the COVID-19-related lockdown on women's mental health and GBV have been reported in low-and middleincome countries 11,16 . A recent German survey reported alarming IPV levels and demonstrated that the COVID-19 Pandemic Leads to a mental health burden even in highly developed Western countries 45 . Another cross-sectional study in the United States showed that during the lockdown, IPV and sexual violence were significantly associated with greater symptom severity of depression and anxiety in the two weeks following the stay-at-home state order 46 .…”
Section: Impact Of Gender-based Violence On Mental Health Amid Covid-19 Pandemicmentioning
confidence: 99%